The Influence of Transformational Leadership Style On Turnover Intention Mediated By Organizational Commitment and Employee Job Satisfaction (Empirical Study: Employees at PT Global Loyalty Indonesia) - Gregorius Reza Triska Yulianto (Asian Journal of Social and Humanities, 2024)
The purpose of this study is to determine the influence of transformational leadership style on turnover intention, as well as to determine the role of organizational commitment and job satisfaction in employees of PT Global Loyalty Indonesia located in Tangerang City. The survey was conducted on 142 respondents who met the respondent criteria using non-probability sampling. The results of this study show that the variable of transformational leadership style has a significant negative effect on turnover intention. The higher the transformational leadership style, the lower the turnover intention in employees. In addition, organizational commitment and job satisfaction can mediate transformational leadership style variables to turnover intention. The limitation of this study is that it only examines the influence of transformational leadership style on turnover intention with organizational commitment and employee job satisfaction as a mediating variable, within the scope of one company, namely PT Global Loyalty Indonesia located in Tangerang City. This research can be generalized more broadly if the samples taken do not only come from one company scope. The implications of this study are expected to provide managerial contributions, especially an overview of experience in choosing a leadership style, as well as its influence on turnover intention, job satisfaction and organizational commitment. So, managers can draw up strategic plans that are in harmony with the internal and external conditions of the company.